Review on Life Cycle Analysis (LCA) Studies to Evaluate the Impact of Waste Managing Aluminium on The Environment - Khairudin, Muhammad Lokman; Yusuf, Nur Kamilah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this recent years, the increased amount of solid waste generation has become a threat to the environmental health which needs immediate attention. Moreover, many waste management methods have developed in order to overcome this problem. Hence, this research project is aimed to review the LCA studies done by researchers on waste management especially aluminium wastes to help decision-makers deciding which is the most suitable waste management methods for them to use. This research project is done by collecting data from literatures such as research papers and articles which are accounted as secondary data. Where this data is then reviewed and analysed to come up with a conclusion. The trend shows that the most preferable aluminium waste managing method was Conventional Recycling. While, some studies show that the new recycling methods which are Direct Recycling (DR) and Semi Direct Recycling (SDR) are more efficient and environmental friendly then the Conventional Recycling method.